TRANSFORMING ISLAMIC EDUCATION THROUGH E-LEARNING AND DIGITAL PLATFORMS: IMPROVING TEACHING, LEARNING, AND STUDENT ENGAGEMENT - Habibullah Habibi; Zabihullah Nadry; Zekrullah Popal; Habibullah Ahmadi (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to explore the awareness, attitudes, and usage of e-learning platforms among Islamic education teachers and students, focusing on how digital tools influence teaching effectiveness and student engagement. A cross-sectional survey was conducted with 100 participants from the Education Faculty of Kabul University. Data were collected using a structured questionnaire covering demographic information, digital literacy, awareness of e-learning tools, attitudes toward digital learning, and frequency of platform usage. Descriptive statistics, cross-tabulation, and correlation analyses were employed to examine relationships between demographic factors and digital platform engagement. The results reveal high levels of awareness and positive attitudes toward e-learning among both teachers and students. Participants recognized the potential of digital platforms to improve learning outcomes and increase engagement. However, challenges such as limited internet access, lack of adequate training, and device shortages were identified as barriers to effective implementation. The study highlights the necessity of integrating technology with traditional teaching methods to maximize educational benefits. The findings implied that digital platforms can significantly transform Islamic education by enhancing engagement, learning efficiency, and accessibility. To ensure successful integration, strategic efforts were required in providing training, improving infrastructure, and adopting blended learning approaches.